The associations between dietary practices and dietary quality, biological health indicators, perceived stress, religiosity, culture, and gender in multicultural Singapore - Ng, Rachel Yi-Xin (2018)
Background: Dietary quality, biological health, culture, religiosity, and perceived stress are co-related. However, there is a dearth of research conducted on Asian populations in secularized and harmonious multicultural societies. Methods: This study addresses these gaps by conducting an investigation in the multicultural and multireligious Singapore to examine the parameters of culture and gender and the associations with (1) dietary quality, (2) biological health indicators, (3) religiosity, and (4) perceived stress. One hundred fifty participants (18–60 years old) were recruited, and their blood pressure (BP), body mass index (BMI), and body fat percentage (BF%) were also measured along with a 5-part questionnaire on demographics, dietary practice, food frequency, religiosity, and perceived stress. Results and conclusion: Results showed that cultural differences are associated with certain dietary practices, where the three ethnic groups of Chinese, Malays, and Indians significantly differed in their choices of meal locations such as Western fast food restaurants (H = 12.369, p = .002061*). Our analysis revealed that perceived stress significantly correlated with fat intake (rs = .169, N = 150, p = .03865) and sugar intake (rs = .172, N = 150, p = .03575). On the other hand, biological parameters such as diastolic BP (rs = −.0473, N = 150, p = .565), systolic BP (rs = −.00972, N = 150, p = .906), BMI (rs = −.0403, N = 150, p = .6246), and BF% (rs = −.110, N = 150, p = .1811) did not have significant correlations with perceived stress. Similarly, religiosity did not significantly correlate with perceived stress (rs = −.025, N = 150, p = .7616). In conclusion, our findings provide insights into the changing intersection of food practices mitigated by ethnicity, religiosity, stress, and gender in the harmonious multiracial and multicultural Singapore.